Morphology and Dimensions of Nasopalatine Canal: a Radiographic Analysis Using Cone Beam Computed Tomography - Leila Khojastepour; Abdolaziz Haghnegahdar; Marzieh Keshtkar (Shiraz University of Medical Sciences, 2017)
Statement of the Problem: The surgical procedure of dental implantation in anterior maxillary area may be limited by the shape and size of nasopalatine canal (NPC). CBCT imaging provides three-dimensional information for surgical planning. Purpose: This study is designed to evaluate the anatomy of NPC in a selected Iranian population. Materials and Method: In this cross sectional study, CBCT images of 301 patients were evaluated for NPC characteristics. Five linear measurements including width and length of NPC were performed on reformatted sagittal cross sections. The shapes of NPC were also classified in three groups according to Bronstein et al. classification in CBCT coronal cross sections. The effects of age and gender on measured dimension were assessed. Student's t-test, one-way ANOVA/Tukey HSD tests, chi-square and Pearson's correlation coefficient were used for statistical analysis. Results: The study comprised 140 males (48.5%) and 161 females (53.5%) with mean age of 34.56±11.87. The mean length of NPC for men and women were 11.46 and 9.37 mm respectively, showing a significant statistical difference. Other dimensions of NPC and alveolar bone thickness were also greater in men with exception of buccal bone plate width in front of Stensen foramen (8.45±2.24 vs. 8.52±2.03 mm).Most of the cases showed Y-shape configuration. The diameter of oral opening of NPC (3.17±1.01 mm) was positively correlated with the patients age (r= 0.138, p= 0.01), while buccal bone over the oral opening of NPC (7.05±1.38) mm showed negative correlation with age (r= -0.199, p= 0.001). Conclusion: All NPC dimensions are meaningfully greater in men except for buccal bone plate thickness in front of Stensen foramen. The type of canal has no effect on dimensions of the canal.